Enlarging the π‐Conjugation of Cobalt Porphyrin for Highly Active and Selective CO2 Electroreduction. Issue 9 (8th April 2021) - Dou, Shuo; Sun, Libo; Xi, Shibo; Li, Xiaogang; Su, Tan; Fan, Hong Jin; Wang, Xin
Abstract: Heterogeneous molecular catalysts have attracted considerable attention as carbon dioxide reduction reaction (CO2 RR) electrocatalysts. The π‐electron system of conjugated ligands in molecular catalysts may play an important role in determining the activity. In this work, by enlarging π‐conjugation through appending more aromatic substituents on the porphyrin ligand, altered π‐electron system endows the as‐prepared 5, 10, 15, 20‐tetrakis(4‐(pyren‐1‐yl)phenyl)porphyrin Co II with high Faradaic efficiency (ca. 95 %) for CO production, as well as high turnover frequency (2.1 s −1 at −0.6 V vs. RHE). Density functional theory calculation further suggests that the improved electrocatalytic performance mainly originates from the higher proportion of Co d z 2 orbital and the CO2 π* orbital in the HOMO of the (Co−porphyrin−CO2 ) − intermediate with larger π‐conjugation, which facilitates the CO2 activation. This work provides strong evidence that π‐conjugation perturbation is effective in boosting the CO2 RR. Abstract : A bigger piece of the π : By enlarging the π‐conjugation of Co−porphyrin molecular electrocatalyst through appending more aromatic substituents at the periphery, the activity and selectivity towards CO2 electroreduction are enhanced. Theoretical study suggests that the higher proportion of Co2 π orbital and the CO2 π* orbital in the HOMO orbital of intermediate with enlarged π‐conjugation facilitate CO2 activation.